2006
DOI: 10.1103/physrevb.73.045425
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulations of the formation and destruction of nanoindentation contacts in tungsten

Abstract: This paper presents atomistic simulations of contact formation, indentation, subsequent pulling, and contact failure between a tungsten tip and a tungsten substrate. Different combinations of ͓111͔ and ͓110͔ crystal directions parallel to the direction of indentation are investigated. The simulations are performed using a Finnis-Sinclair potential for tungsten and a displacement controlled, quasistatic simulation scheme. The simulation setup and the tip geometry are inspired by low temperature scanning tunneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 45 publications
4
34
1
Order By: Relevance
“…Adhesion forces also play a role in retraction; as the tip retracts from the sample, a connective neck of atoms forms between the substrate and the tip. MD simulations also suggested that material transfer usually occurs during contact separation [30]. A similar phenomenon was found by Oliver et al [100] when they performed one-to-one spatially matched experiment and atomistic simulations of nanometre-scale indentation; they reported that many features of the experiment were correctly reproduced by MD simulations, in some cases only when an atomically rough indenter rather than a smooth repulsive-potential indenter is used, tip wetting being one of these features.…”
Section: Role Of Adhesive Forces and Tip Wettingsupporting
confidence: 65%
See 1 more Smart Citation
“…Adhesion forces also play a role in retraction; as the tip retracts from the sample, a connective neck of atoms forms between the substrate and the tip. MD simulations also suggested that material transfer usually occurs during contact separation [30]. A similar phenomenon was found by Oliver et al [100] when they performed one-to-one spatially matched experiment and atomistic simulations of nanometre-scale indentation; they reported that many features of the experiment were correctly reproduced by MD simulations, in some cases only when an atomically rough indenter rather than a smooth repulsive-potential indenter is used, tip wetting being one of these features.…”
Section: Role Of Adhesive Forces and Tip Wettingsupporting
confidence: 65%
“…Prismatic loops are also formed in bcc metals, as was observed by Hagelaar et al [30] during nanoindentation in tungsten. Upon indentation on a (111) surface loop generation was associated with shear stresses in their atomistic indenter.…”
Section: Bcc Metalssupporting
confidence: 64%
“…Reducing the indentation velocity to 3.4 m s À1 did not produce any qualitative change in loading curves and plasticity, but lowered slightly the plastic threshold, as expected. Quasistatic simulations as in Hagelaar et al [25] might lead to somewhat different results. Of course, simulated speeds are orders of magnitude larger than experimental values, and there might be effects due to the high strain rate of every MD simulation, for instance in dislocation-twinning competition [34].…”
Section: Methodsmentioning
confidence: 95%
“…In one of the first MD simulations for indentation of body-centered cubic (bcc) metals, tungsten was investigated using a Finnis-Sinclair potential with $850,000 atoms, [1 1 1] and [1 1 0] surfaces, and a tip diameter of 10 nm [25]; penetration depths were limited due to the relatively small sample size, but allowed the observation of the earlier stages of plastic activity, often including emission of prismatic loops. Kumar et al [26] recently simulated Fe, pure and with impurities, using $1 million atoms, a 4 nm diameter indenter and velocity of 100 nm ps À1 , showing that slip occurs in {1 1 0}, {1 1 2} and {1 2 3} planes, as expected from bcc crystal symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there wasn't any robust interaction potential energy function between carbon and tantalum (to the best of our knowledge) and hence, spherical indenter was filled with the tantalum atoms to describe the chemical interactions. While such an assumption is not novel [21], it was ensured prior to this study that our results on dislocation mechanics and yielding stresses are not out of order with such an assumption. Accordingly, we have performed an extensive stress and dislocation mechanics analysis and have found that this consideration can predict the Tresca yielding stress of the substrate to be in close proximity of what would have otherwise predicted by a rigid diamond indenter.…”
Section: Molecular Dynamics Simulation Of Nanoindentationmentioning
confidence: 99%